57 Channels (And Nothin On): Does TV-News on the Eurozone affect Government Bond Yield Spreads? - Julia Wolfinger; Ekkehard A. Köhler; Lars P. Feld; Tobias Thomas (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This article empirically investigates the relationship between TV news coverage on the eurocrisis and the GIIPS countries bond yield spreads with daily data between January 1, 2007 and December 1, 2016. We use 1,542,233 human coded news items from evening news shows of leading TV stations in 12 countries. These news items include 37,859 news on the EU, on the Eurozone and on country-specific economic issues related to the GIIPS countries and Germany. We find that an increasing share of news about the Eurozone reduces yield spreads, especially when the news has a positive tonality. This, at least in the short run, hints at the effectiveness of political communication through the media by European institutions and in particular the European Central Bank (ECB). In conjunction with the tonality of the news, we find some hints on country-specific news to have a significant impact on GIIPS yield spreads. A higher share of positive/negative news is positively associated with a decrease/increase the GIIPS yield spreads vis-`a-vis Germany. Despite these hardly surprising results, we find some evidence that some news is not immediately and completely priced in by market participants when it is released: we still find a significant effect of prior days news on the GIIPS bond yield spreads. In addition, we find that this peculiar effect of country specific news is stronger when the respective news is aired on the North American media market. We explain this higher coefficient as follows: North American TV news air only those news that are truly surprising and have thus a strong effect on yield spreads
Keywords: E58; G12; L8; N14; E58; G12; L8; N14; 330; Eurozone; Euro; political communication; media coverage; yield spreads; dynamic macro panel; FGLS